Correction to: Development and Validation of an Obstetric Comorbidity Risk Score for Clinical Use by Ruppel et al. Womens Health Rep. 2021; 2:507?515. DOI: 10.1089/whr.2021.0046. (Mary Ann Liebert, 2021)
In the 2021 issue of Women's Health Reports (vol. 2, no. 1; pp. 507?515), the article entitled ?Development and Validation of an Obstetric Comorbidity Risk Score for Clinical Use? by Ruppel et al. requires correction. On page 514, additional information has been added to the Funding Information section. The original sentence published as: H.R. was supported by the Building Interdisciplinary Research Careers in Women's Health (BIRCWH) program, NIH/NICHD/ORWH K12 HD052163. V.X.L. was supported by NIH R35GM128672. The funding source had no role in the study design, collection, analysis, or interpretation of data, writing the report, or decision to submit article for publication. This has been revised to: H.R. was supported by the Building Interdisciplinary Research Careers in Women's Health (BIRCWH) program, NIH/NICHD/ORWH K12 HD052163. V.X.L. was supported by NIH R35GM128672. This work was supported by The Permanente Medical Group, Inc., and Kaiser Foundation Hospitals, Inc. The funding source had no role in the study design, collection, analysis, or interpretation of data, writing the report, or decision to submit article for publication. The online version has been corrected to reflect this. The publisher apologizes for this error.